Properties of polarization radiation from charged particles beam brushing surface of a solid. (July 2016) - Tishchenko, Alexey A.; Sergeeva, Daria Yu.; Strikhanov, Mikhail N.
Abstract: We consider theoretically the electromagnetic radiation from a bunch of charged particles moving parallel or almost parallel to the surface of a solid, in conditions when the distance between the centre of the bunch and the surface is less than the transversal bunch size (beam brushes the surface). The radiation resulting proves to be a mixture of transition radiation and diffraction radiation. We obtain for the first time the expression for incoherent form-factor for Gaussian distribution of the bunch, and demonstrate that it plays a key role in case of a beam brushing the surface. Highlights: Beam brushing a surface proves to radiate both transition and diffraction radiation. Radiation intensity is maximal when the whole beam moves just under the surface. The form-factor of the beam is defined by its size and the properties of a solid.